The right to refuse: The Victorian Mental Health Act 2014 and the Convention on the Rights of Persons with Disabilities. (June 2017) - Maylea, Chris; Hirsch, Asher
This article considers how the Victorian Mental Health Act 2014 extinguishes the right of people with a mental illness to refuse treatment in light of the Convention on the Rights of Persons with Disabilities, which prohibits detention or compulsory treatment on the basis of a person's disability. Three possible resolutions of this inconsistency are proposed and considered: repealing the Mental Health Act 2014, de-linking disability from compulsory treatment, and maintaining legal capacity by supporting mental capacity.